Cold forging steel

A steel composition with controlled components and annealing conditions ensures uniform dispersion of spheroidal carbides, addressing non-uniform deformation and cracking issues in cold forging, achieving excellent cold forging properties.

JP7628446B2Active Publication Date: 2025-02-10SANYO SPECIAL STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021044020
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-02-10
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

The non-uniform distribution of spheroidized cementite in the spheroidized annealed structure of hypoeutectoid steel leads to non-uniform deformation during cold forging, promoting cracking and reducing workability.

Method used

A steel composition with specific components, including C, Si, Mn, Cr, Al, N, and optional additions of Ni, Mo, Nb, Ti, and V, is used to promote uniform dispersion of spheroidal carbides throughout the structure by adjusting C diffusion behavior and incorporating fine particles as nuclei during spheroidizing annealing.

Benefits of technology

The steel achieves uniform dispersion of spheroidal carbides, preventing cracking during cold forging and ensuring excellent cold forging properties with hardness below 83HRB, allowing high compression without failure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628446000005
    Figure 0007628446000005
  • Figure 0007628446000006
    Figure 0007628446000006
  • Figure 0007628446000007
    Figure 0007628446000007
Patent Text Reader

Abstract

To provide a hypo-eutectoid steel that has spherical carbides uniformly dispersed over the whole tissue and can resist cracking during cold forging.SOLUTION: A steel for cold forging comprises, in mass%, C: 0.14-0.45%, Si: 0.05-1.00%, Mn: 0.10-0.90%, Cr: 1.30-3.50%, Al: 0.020-0.200%, N: 0.0040-0.0300%, with the balance being Fe and unavoidable impurities. P and S as unavoidable impurities are P: 0.030% or less and S: 0.030% or less. The A1 point is 750°C or higher. The steel structure before spheroidizing is a tissue comprising two phases of a ferrite phase and a pearlitic phase, a tissue comprising two phases of a ferrite phase and a bainite phase, and a tissue comprising three phases of a ferrite phase, a pearlitic phase and a bainite phase. The area ratio of fine particles among ferrite grains is 1.0% or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hypoeutectoid steel for cold forging, and in particular to a steel that has excellent cold forgeability when cold forging is used for forming parts, due to the uniform dispersion of spheroidized carbides throughout the steel as a result of spheroidizing annealing. [Background technology]

[0002] When hypoeutectoid steel, which is a low carbon steel, is processed to form parts, cold forging is sometimes selected from the viewpoint of improving yield and production efficiency. In addition, when cold forging is performed, spheroidizing annealing is usually performed to reduce deformation resistance.

[0003] The spheroidizing annealing of hypo-eutectoid steel usually involves the following steps: (Step 1) Raise the temperature to the A1 point or higher. (Step 2) Hold the temperature at or above the A1 point to create a structure consisting of two phases, ferrite and austenite. (Step 3) After that, slowly cool from just above the A1 point to just below the A1 point in order to suppress the austenite to pearlite transformation. At this time, spheroidized cementite precipitates at the austenite / ferrite interface of the two-phase structure, and after slow cooling to just below A1 is completed, a structure is formed in which spheroidized cementite precipitates within the ferrite grains.

[0004] In the spheroidized annealed structure of hypo-eutectoid steel, uneven distribution of spheroidized cementite after slow cooling may occur due to the process of holding the structure in the two-phase region consisting of the ferrite phase and the austenite phase in (Step 2). Such uneven distribution of cementite is undesirable from the viewpoint of workability because it promotes uneven deformation during cold forging and is one of the causes of cracking.

[0005] In conventional steel materials with excellent cold forgeability, for example, case-hardened steel materials have been proposed that aim to improve cold forgeability by appropriately controlling the area ratios of ferrite, bainite, and pearlite before spheroidizing annealing to balance the shape, density, and dispersion state of spheroidized carbides after spheroidizing annealing (see Patent Document 1).

[0006] In addition, a steel wire rod or bar for case hardening has been proposed in which fine carbides caused by bainite are dispersed after spheroidizing annealing by ensuring an appropriate bainite area ratio before spheroidizing annealing, thereby improving cracking (see Patent Document 2).

[0007] In addition, a case-hardened steel for cold forging has been proposed in which, in a structure consisting of two phases, ferrite and pearlite, before spheroidizing annealing, the ferrite grains and pearlite grains are made smaller to increase the ferrite / pearlite grain boundaries and promote cementite precipitation at the interfaces, thereby shortening the spheroidizing annealing time and uniformly dispersing cementite, thereby ensuring cold forgeability (see Patent Document 3). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2014-185389 A [Patent Document 2] JP 2005-220377 A [Patent Document 3] Japanese Patent Application Publication No. 11-012684 Summary of the Invention [Problem to be solved by the invention]

[0009] In the spheroidized annealed structure of hypo-eutectoid steel, uneven distribution of spheroidized cementite after slow cooling may occur due to the above-mentioned (Step 2) step of maintaining the structure in the two-phase region of ferrite and austenite. Since such uneven distribution of cementite promotes uneven deformation during cold forging and is one of the causes of cracking, it is desirable to have a uniform distribution of cementite from the viewpoint of workability.

[0010] Although the proposals in the above-mentioned prior art attempt to optimize the shape and dispersion state of spheroidized cementite after spheroidizing annealing, all of them are merely proposals to appropriately control the structure before spheroidizing annealing. In other words, when looking at the inside of ferrite grains in a structure consisting of two phases, ferrite phase and austenite phase, in (Step 2) in the normal spheroidizing annealing process, spheroidized cementite cannot be precipitated, and therefore it cannot be said that they adequately deal with the prevention of non-uniform distribution of spheroidized cementite.

[0011] Therefore, the problem to be solved by the present invention is to provide a steel for cold forging in which spheroidized carbides are uniformly dispersed throughout the structure, and cracks during cold forging can be suppressed. [Means for solving the problem]

[0012] The inventors of the present application have conducted extensive research focusing on the C diffusion behavior just below the austenitizing temperature. In conventional hypoeutectoid steels, solute C in ferrite grains stably precipitates as M3C carbides (cementite) just below the austenitizing temperature. Therefore, C exists as M3C carbides in both pearlite grains (structures composed of ferrite and lamellar cementite) and bainite grains (structures composed of ferrite and cementite) and ferrite grains (cementite is stably precipitated). As a result, it is difficult to create a difference in C diffusion behavior, and sufficient driving force for C diffusion from pearlite grains and bainite grains to ferrite grains cannot be obtained.

[0013] On the other hand, by using a high Cr content, the solute C in the ferrite grains stably precipitates as M7C3 type (M = Fe and Cr mixed components) carbides just below the austenitization temperature. In other words, the difference in C diffusion behavior between pearlite grains (structures composed of ferrite and lamellar cementite) and bainite grains (structures composed of ferrite and cementite) and ferrite grains (M7C3 carbides are stable) becomes large. As a result, it was found that the C diffusion from pearlite grains and bainite grains to ferrite grains is sufficiently promoted.

[0014] In addition, it was found that in order for a sufficient amount of solute C that has flowed into the ferrite grains to precipitate as spheroidized carbides, a certain amount of fine particles (such as Al nitrides, Nb carbonitrides, V carbonitrides, and Ti carbonitrides) that act as precipitation nuclei within the ferrite grains are required.

[0015] In other words, the main reason why the steel of the present invention can be suitably applied to cold forging by further spheroidizing annealing is that, by adjusting the components of the test material, the diffusion of C from pearlite grains and bainite grains to ferrite grains just below the austenitizing temperature is promoted, and a certain amount or more of fine particles such as AlN, which act as precipitation nuclei for spheroidized carbides within the ferrite grains, are precipitated.

[0016] Furthermore, the inventors discovered that by adjusting the composition of the steel, the stable carbides within the ferrite grains just below the austenitization temperature are made to be of the M7C3 type, which makes it easier to uniformly disperse spheroidized carbides.

[0017] In this way, the inventors of the present application have discovered that by further subjecting a steel having a specified chemical composition to a specified spheroidizing annealing, it is possible to obtain a steel in which spheroidized carbides are uniformly dispersed throughout the structure, thereby suppressing cracking during cold forging.

[0018] The steel of the present invention has a structure before heat treatment consisting of two phases, ferrite and pearlite, two phases, ferrite and bainite, or three phases, ferrite, pearlite and bainite. When the steel of the present invention is used, (a) during holding at just below the austenitizing temperature, lamellar cementite constituting pearlite and cementite constituting bainite are dissolved and spheroidized, (b) solute C flows into the ferrite grains, (c) M7C3 type carbides precipitate in the ferrite grains, and (d) these grow into spheroidized carbides, thereby obtaining a steel in which spheroidized carbides are uniformly dispersed throughout. Here, the M7C3 type carbides are a mixed component of M=Fe and Cr.

[0019] From the above, the first means for solving the problems of the present invention is In mass%, C: 0.14-0.45%, Si: 0.05 to 1.00%, Mn: 0.10-0.90%, Cr: 1.30~3.50%, Al: 0.020~0.200%, N: 0.0040~0.0300%, The balance is Fe and unavoidable impurities. The amounts of P and S as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A1 point is 750°C or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases: ferrite and pearlite. A structure consisting of two phases: ferrite and bainite. Or a structure consisting of three phases: ferrite, pearlite, and bainite, Cold forging steel with fine grain area ratio of 1.0% or more in ferrite grains It is.

[0020] The second method is In addition to the chemical components described in the first aspect, the alloy contains at least one of Ni: 0.02 to 2.00% and Mo: 0.02 to 2.00%; The balance is Fe and unavoidable impurities. The amounts of P and S as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A1 point is 750°C or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases: ferrite and pearlite. A structure consisting of two phases: ferrite and bainite. Or a structure consisting of three phases: ferrite, pearlite, and bainite, Cold forging steel with fine grain area ratio of 1.0% or more in ferrite grains It is.

[0021] The third method is In addition to the chemical components described in the first or second means, Contains one or more of Nb: 0.02-0.10%, Ti: 0.020-0.200%, B: 0.0010-0.0050%, and V: 0.010-0.500%, The balance is Fe and unavoidable impurities. The amounts of P and S as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A1 point is 750°C or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases: ferrite and pearlite. A structure consisting of two phases: ferrite and bainite. Or a structure consisting of three phases: ferrite, pearlite, and bainite, Cold forging steel with fine grain area ratio of 1.0% or more in ferrite grains It is. Effect of the Invention

[0022] When the cold forging steel of the present invention is spheroidized annealed, the area ratio of ferrite grains in which no spheroidized carbides have precipitated (when the number of spheroidized carbides with an equivalent circle diameter of 0.5 μm or more present in a grain is defined as "a ferrite grain in which no spheroidized carbides have precipitated") is within 6.0% of the entire structure, and the area ratio of the remaining pearlite grains and bainite grains after spheroidized annealing is also 5.0% or less, indicating that the spheroidization of the carbides is sufficiently advanced. As a result, the steel does not crack even when subjected to high compression during cold forging. That is, when the steel for cold forging of the present invention is spheroidized, the hardness is 83 HRB or less, and cold working can be performed without cracking even when cold forging is performed at a cold upset rate of 75%, and the steel for cold forging of the present invention can exhibit excellent cold forgeability after spheroidized annealing.

[0023] In other words, by subjecting the cold forging steel of the present invention to spheroidizing annealing, the steel becomes structured in such a way that spheroidized carbides are uniformly dispersed throughout, which has the effect of preventing the steel from cracking even under high compression during cold forging, thereby making it possible to obtain a steel that exhibits excellent cold forgeability. [Brief description of the drawings]

[0024] [Figure 1] FIG. 2 is a schematic diagram for explaining the temperature history of the holding temperature T (° C.), holding time (hr), and air cooling under the spheroidizing annealing conditions. [Diagram 2] The image observed by a transmission electron microscope (TEM) and the area ratio of fine particles are shown. [Diagram 3] The optical microscope photographs and the area ratio of ferrite grains without spheroidized carbide precipitation and the area ratio of remaining pearlite and bainite are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Before describing the embodiment of the steel according to the present invention, the reasons for specifying the composition of the steel, the reasons for specifying the lower limit of the A1 point, and the reasons for specifying the area ratio of fine particles in ferrite grains will be described. Note that % in the following composition is mass %.

[0026] C: 0.14-0.45% C is an element that improves the hardness of the material. If the C content is less than 0.14%, the core hardness after carburization decreases, resulting in insufficient strength. On the other hand, if the C content exceeds 0.45%, the material hardness increases too much, reducing workability, resulting in poor machinability and cold forgeability. Therefore, the C content is set to 0.14 to 0.45%, and preferably 0.14 to 0.30%.

[0027] Silicon: 0.05 to 1.00% Silicon is a useful element for deoxidization. If the silicon content is less than 0.05%, there will be a shortage of deoxidizing material. On the other hand, if the silicon content exceeds 1.00%, the material hardness will increase too much, reducing workability, and carburization will be inhibited. Therefore, the Si content is set to 0.05 to 1.00%, and preferably, the Si content is set to 0.30 to 0.80%.

[0028] Mn: 0.10 to 0.90% Mn is an element that improves hardenability. If the Mn content is less than 0.10%, hardening will be insufficient. On the other hand, if the Mn content exceeds 0.90%, workability will decrease. Therefore, the Mn content is 0.10 to 0.90%, and preferably 0.15 to 0.50%.

[0029] Cr: 1.30~3.50% Cr is an element that stabilizes M7C3 type carbides. If Cr is less than 1.30%, M7C3 type carbides do not precipitate, so that the amount of C that flows from pearlite grains and bainite grains to ferrite grains during spheroidizing annealing is insufficient, and the distribution of spheroidized carbides becomes non-uniform, resulting in a decrease in cold forgeability. In addition, hardenability is insufficient. On the other hand, if Cr exceeds 3.50%, the material hardness increases too much, resulting in a decrease in workability. In addition, carburization inhibition occurs. Therefore, Cr is set to 1.30 to 3.50%. Desirably, Cr is 1.40 to 2.50%.

[0030] Al: 0.020~0.200% Al is an element useful for deoxidization. If Al is less than 0.020%, it will be insufficient as a deoxidizer. In addition, since there will be a shortage of fine nitrides, there will be a shortage of precipitation nuclei for M7C3 type carbides, and the toughness and fatigue properties will decrease due to the coarsening of crystal grains. On the other hand, if Al exceeds 0.200%, coarse nitrides will be formed, and the fatigue properties and workability will decrease. Therefore, Al is set to 0.020 to 0.200%. Desirably, Al is set to 0.020 to 0.050%.

[0031] N: 0.0040~0.0300% N is an element that forms nitrides. If N is less than 0.0040%, fine nitrides are insufficient, resulting in a shortage of precipitation nuclei for M7C3, and the toughness and fatigue properties are reduced due to the coarsening of crystal grains. On the other hand, if N exceeds 0.0300%, coarse carbonitrides are formed, resulting in a deterioration of fatigue properties and workability. Therefore, N is set to 0.0040 to 0.0300%. Desirably, N is set to 0.0040 to 0.0200%.

[0032] P: 0.030% or less as unavoidable impurities If the P content exceeds 0.030%, the toughness decreases due to grain boundary segregation, so even if P is contained as an unavoidable impurity, the content is set to 0.030% or less.

[0033] S: 0.030% or less as unavoidable impurities If the S content exceeds 0.030%, MnS is formed, which reduces the toughness and fatigue strength. Therefore, even if S is contained as an unavoidable impurity, the S content is set to 0.030% or less.

[0034] The following components describe optional ingredients that may be optionally added. Ni: 0.02 to 2.00% Ni is an element that improves hardenability and toughness. If Ni is less than 0.02%, the effect of improving hardenability is small, and the effect of improving toughness is also small. On the other hand, if Ni is added in an amount exceeding 2.00%, not only will the cost increase, but the material hardness will also increase, resulting in a decrease in workability. Therefore, when Ni is added, it is set to 0.02 to 2.00%. Preferably, the amount of Ni added is 0.02 to 1.80%.

[0035] Mo: 0.02 to 2.00% Mo is an element that improves hardenability. If Mo is less than 0.02%, the effect of improving hardenability is small. On the other hand, if Mo exceeds 2.00%, in addition to increasing costs, the material hardness also increases, resulting in reduced workability. Therefore, when Mo is added, it is set to 0.02 to 2.00%. Desirably, the amount of Mo added is 0.02 to 0.50%.

[0036] Nb: 0.02 to 0.10% Nb is an element that generates carbonitrides and suppresses grain coarsening. If the Nb content is less than 0.02%, the amount of fine carbonitrides is insufficient, so the effect of suppressing grain coarsening is reduced, and the toughness and fatigue strength are insufficient. On the other hand, if the Nb content exceeds 0.10%, the amount of carbonitrides becomes excessive and the workability is reduced. Therefore, when Nb is added, it is set to 0.02 to 0.10%. Desirably, the amount of Nb added is 0.02 to 0.08%.

[0037] Ti: 0.020~0.200% Ti is an element that generates carbonitrides and suppresses grain coarsening. If Ti is less than 0.020%, the amount of fine nitrides is insufficient. In addition, N is not fixed and forms BN, which reduces hardenability. In addition, the effect of suppressing grain coarsening is reduced. On the other hand, if the Ti content exceeds 0.200%, the amount of carbonitrides becomes excessive, resulting in a decrease in workability. Therefore, when Ti is added, the content is set to 0.020 to 0.200%, and preferably, the content of Ti added is set to 0.020 to 0.100%.

[0038] B: 0.0010~0.0050% B is an element that improves hardenability. If B is less than 0.0010%, the effect of improving hardenability is small. If B exceeds 0.0050%, the workability decreases due to an increase in material hardness. Therefore, when B is added, the content is set to 0.0010 to 0.0050%. Preferably, the amount of B added is 0.0010 to 0.0030%.

[0039] V: 0.010~0.500% V is an element that generates carbonitrides and suppresses grain coarsening. If V is less than 0.010%, fine carbonitrides are insufficient and the effect of suppressing grain coarsening is small, resulting in insufficient toughness and fatigue strength. On the other hand, if V exceeds 0.500%, the amount of carbonitrides becomes excessive and workability decreases. Therefore, when V is added, it is set to 0.010 to 0.500%. Desirably, V is added in an amount of 0.010 to 0.400%.

[0040] A1 point: 750℃ or higher If the A1 point is less than 750°C, the holding temperature for spheroidizing annealing will be low, and the spheroidization of the carbides that compose pearlite and bainite will be insufficient. As a result, the cold workability will decrease due to insufficient softening. Therefore, the A1 point is set to be equal to or higher than 750° C. More preferably, the A1 point is set to be 750 to 800° C. In addition, A1 in the present invention can be calculated using Ac1 = 723°C-14Mn[%] + 22Si[%] - 14.4Ni[%] + 23.3Cr[%].

[0041] Area ratio of fine particles in ferrite grains: 1.0% or more If the area ratio of fine particles in the ferrite grains of the steel structure before spheroidizing annealing is less than 1.0%, the precipitation nuclei of the spheroidized carbides that precipitate in the ferrite grains will be insufficient. Therefore, the steel structure before spheroidizing annealing is either a structure consisting of two phases, ferrite and pearlite, a structure consisting of two phases, ferrite and bainite, or a structure consisting of three phases, ferrite, pearlite and bainite, and the area ratio of fine particles in the ferrite grains is set to 1.0% or more.

[0042] <Manufacturing process of test material> Inventive steels No. 1 to 22 in [Table 1] and comparative steels No. 1 to 11 each having the chemical components described therein with the balance being Fe were melted in a 100 kg vacuum induction furnace (VIM) to produce steel ingots, which were then forged to φ32 at 1250°C, normalized at 925°C for 1 hour, and then cut to 100 mm to obtain test specimens.

[0043] [Table 1]

[0044] [Table 2]

[0045] (Measurement of the amount of fine particles in ferrite grains) For each test material, samples for TEM were prepared from the D / 4 position using the extraction replica method, and the samples were then observed using a transmission electron microscope (TEM). For each test material sample, a total of five fields of view (approximately 9 μm × 9 μm) were photographed, and the fine particles present in each field of view were subjected to image analysis to calculate the area ratio of fine particles with a circle equivalent diameter of 300 nm or less. The results are shown in Table 3. Figure 2 shows the TEM images and the area ratio of fine particles of inventive steel 6, inventive steel 21, and comparative example 3.

[0046] 2, the area ratio of fine particles was 2.2% for Inventive Steel 6 and 3.7% for Inventive Steel 21, while it was 0.3% for Comparative Example 3. In the steel of the present invention, there are sufficient fine particles that serve as precipitation nuclei in the ferrite grains, so when this steel is annealed, the solute C that has flowed into the ferrite grains can precipitate in a sufficient amount as spheroidized carbides.

[0047] (Spheroidizing annealing process) The test material prepared above was subjected to spheroidizing annealing using a Kanthal furnace according to the following procedure: The test material was placed in a furnace set to the holding temperature for spheroidizing annealing according to the holding temperature T and holding time t shown in Tables 3 and 4, the test material was allowed to heat up for 30 minutes, and was held for the specified time, after which it was air-cooled.

[0048] [Table 3]

[0049] [Table 4]

[0050] (Spheroidizing annealing conditions) A schematic diagram for explaining the holding temperature T (°C) and holding time t (hr) of the temperature history, which are the spheroidizing annealing conditions, is shown in Figure 1. The holding temperature T and holding time t conditions when spheroidizing annealing the steel of the present invention can be reliably determined by satisfying the following [Equations 1] to [Equations 3]. [Formula 1]: (A1 point -30℃)≦T≦(A1 point -5℃) [Formula 2]:t≧120 / (T-A1+50) [Formula 3]: A1=723℃-14Mn[%]+22Si[%]-14.4Ni[%]+23.3Cr[%]

[0051] (Measurement of the area ratio of ferrite grains where no spheroidized carbides are precipitated) After spheroidizing annealing, the test pieces were cut out from the D / 4 position, embedded in resin, polished, and the surface was etched with a nital etching solution. Five fields of view were then observed under an optical microscope at 400x magnification, and the area ratio was calculated by image analysis. In addition, when the number of spheroidal carbides having an equivalent circle diameter of 0.5 μm or more present in a ferrite grain is less than 5, the ferrite grain is defined as "a ferrite grain in which no spheroidal carbides are precipitated." As a result of measuring the area ratio of ferrite grains in which no spheroidized carbides were precipitated in the observation field after spheroidizing annealing, it can be said that those exceeding 6.0% of the whole structure are insufficiently spheroidized or not uniformly dispersed. The results are shown in Tables 3 and 4.

[0052] (Measurement of area ratio of remaining pearlite grains and bainite grains) Similarly, the test material after spheroidizing annealing was observed in five fields of view using an optical microscope at a magnification of 400 times, and calculations were made by image analysis. When the area ratio of the remaining pearlite grains and bainite grains after spheroidizing annealing is 5.0% or less, it can be said that the spheroidization of the carbides has progressed sufficiently, but when the area ratio of the remaining pearlite grains and bainite grains exceeds 5.0%, it can be said that the spheroidization of the carbides is insufficient, and the cold forgeability is reduced due to insufficient softening. The results are shown in Tables 3 and 4.

[0053] FIG. 3 shows optical microscope photographs of inventive steel 6, inventive steel 21, comparative steel 1, and comparative steel 3 after spheroidizing annealing, as well as the area ratios of ferrite grains in which no spheroidized carbides were precipitated, and the area ratios of remaining pearlite grains and bainite grains.

[0054] (Hardness measurement) The hardness of the spheroidized annealed steel bar material at the midpoint between the center and the outer circumference (called "D / 4" where D represents the diameter) was measured using a Rockwell hardness tester and taken as the hardness (HRB). If the spheroidized annealing hardness exceeds 83HRB, the cold forging deformability decreases, and cracks are likely to occur when cold forging is performed at a high processing rate. Therefore, it is desirable to set the spheroidized annealing hardness to 83HRB or less. The results are shown in Tables 3 and 4.

[0055] (Presence or absence of cracks at 75% cold upsetting) Cylindrical test pieces measuring φ14×21 mm were prepared from the center of the test material (the forging direction of the test material was parallel to the longitudinal direction of the test piece). Using these cylindrical test pieces, cold upsetting tests were carried out at room temperature. The upsetting speed was 10 mm / min, and the final upsetting rate (reduction rate of the height of the test piece) was 75%, and the test pieces were inspected for the presence or absence of surface cracks after processing. The results are shown in Tables 3 and 4.

[0056] The invention steels 1 to 22 had chemical compositions within the ranges specified by the present invention, had A1 points of 750° C. or higher, and had an area ratio of fine particles in ferrite grains of 1.0% or higher. It was confirmed that, since there were sufficient fine particles to serve as nuclei, when these were spheroidized and annealed, the solid solution C that had flowed into the ferrite grains precipitated in sufficient amounts as spheroidized carbides, and that the area of ​​the ferrite grains in which the spheroidized carbides did not precipitate within the grains after spheroidized annealing was 6% or less, and the area ratio of the remaining pearlite grains and bainite grains was also 5% or less, sufficient spheroidized carbides precipitated, and the cold forgeability was excellent. It was also confirmed that, when the cold forging steels of invention steels 1 to 22 were spheroidized and annealed, the hardness was 83HRB or less, and no cracks were observed in a 75% cold upset test, so that excellent cold workability was obtained.

[0057] When the steel of the present invention is spheroidized annealed, M7C3 carbides precipitate within the prior ferrite grains, resulting in a structure in which the spheroidized carbides are uniformly dispersed throughout. This is believed to result in the precipitation of uniformly dispersed spheroidized carbides, resulting in excellent cold forgeability.

[0058] Comparative steels 1, 2, 5, and 7 had insufficient Cr and an A1 point below 750°C. After spheroidizing annealing, the area of ​​ferrite grains without intragranular precipitation of spheroidized carbides was 38% or more, and the area ratio of the remaining pearlite grains and bainite grains was also 20% or more. As a result, the spheroidization of the carbides that make up pearlite and bainite was insufficient, and cold forgeability was reduced due to insufficient softening, and cracks were confirmed in a 75% cold upset test. In comparative steels 3 and 4, the Al content was too low, the area ratio of fine particles within the ferrite grains was less than 1.0%, and there were insufficient precipitation nuclei for the spheroidized carbides that precipitate within the ferrite grains. As a result, the area ratio of the remaining pearlite grains and bainite grains after spheroidizing annealing was also 25% or more, resulting in insufficient spheroidization of the carbides that make up the pearlite and bainite, and insufficient softening, which reduced cold forgeability and confirmed cracks in the 75% cold upset test. In comparative steel 6, the Al content was too low, the area ratio of fine particles within the ferrite grains was less than 1.0%, and there were insufficient precipitation nuclei for the spheroidized carbides that precipitated within the ferrite grains, so the area of ​​ferrite grains without intragranular precipitation of spheroidized carbides was 8% or more, and the area ratio of the remaining pearlite grains and bainite grains after spheroidizing annealing was also 25% or more. As a result, the spheroidization of the carbides that make up pearlite and bainite was insufficient, and the cold forgeability was reduced due to insufficient softening, and cracks were confirmed in the 75% cold upset test. Comparative Example 8 had an excessive amount of Cr, was hard at 84 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 9 contained excessive amounts of Mn and Cr, was hard at 85 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 10 had an excessive amount of Si, was hard at 85 HRB, and cracks were observed in the 75% cold upset test. Comparative Example 11 had excessive amounts of C and Mo, was hard at 86 HRB, and cracks were observed in the 75% cold upset test.

Claims

1. In mass percent, C: 0.14-0.45%, Si: 0.05-1.00%, Mn: 0.10-0.90%, Cr: 1.30-3.50%, Al: 0.020-0.200%, N: 0.0040-0.0300%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases, ferrite and pearlite, A structure consisting of two phases, ferrite and bainite. Or a structure consisting of three phases: ferrite phase, pearlite phase, and bainite phase, A steel for cold forging, in which the area ratio of fine particles within ferrite grains is 1.0% or more.

2. In addition to the chemical components described in claim 1, the alloy contains at least one of Ni: 0.02 to 2.00% and Mo: 0.02 to 2.00%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases, ferrite and pearlite, A structure consisting of two phases, ferrite and bainite. Or a structure consisting of three phases: ferrite phase, pearlite phase, and bainite phase, A steel for cold forging, in which the area ratio of fine particles within ferrite grains is 1.0% or more.

3. In addition to the chemical components according to claim 1 or 2, Contains one or more of Nb: 0.02 to 0.10%, Ti: 0.020 to 0.200%, B: 0.0010 to 0.0050%, and V: 0.010 to 0.500%, The balance is Fe and unavoidable impurities. The P and S contents as inevitable impurities are P: 0.030% or less and S: 0.030% or less, A 1 The point is 750° C. or higher, The steel structure is in a state before spheroidizing annealing, A structure consisting of two phases, ferrite and pearlite, A structure consisting of two phases, ferrite and bainite. Or a structure consisting of three phases: ferrite phase, pearlite phase, and bainite phase, A steel for cold forging, in which the area ratio of fine particles within ferrite grains is 1.0% or more.

Citation Information

Patent Citations

  • Case hardening steel for cold forging

    JP1999012684A

  • Steel wire rod or bar steel for case hardening having excellent cold forgeability after spheroidizing

    JP2005220377A

  • Hot-rolled material having superior properties of preventing crystal grain from coarsening when carburized at high temperature

    JP2007321211A

  • Steel material for case hardening and gear excellent in surface fatigue strength and cold forgeability

    JP2014185389A

  • Case hardening steel excellent in cold forgeability and crystal grain coarsening suppression performance

    JP2015166495A